2013
DOI: 10.1021/jp3128516
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Induced Destruction of Bacterial Cell Wall Components: A Reactive Molecular Dynamics Simulation

Abstract: Nonthermal atmospheric pressure plasmas are gaining increasing attention for biomedical applications. However, very little fundamental information on the interaction mechanisms between the plasma species and biological cells is currently available. We investigate the interaction of important plasma species, such as OH, H 2 O 2 , O, O 3 , as well as O 2 and H 2 O, with bacterial peptidoglycan by means of reactive molecular dynamics simulations, aiming for a better understanding of plasma disinfection. Our resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
120
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 156 publications
(139 citation statements)
references
References 34 publications
17
120
0
2
Order By: Relevance
“…In contrast, a study by Mozetic et al . has clearly shown damage by CAP treatment to the cell wall of Bacillus stearothermophilus before the plasma membrane was damaged37 and further indications that the bacterial cell wall is an important target during plasma interaction have been reported1314.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In contrast, a study by Mozetic et al . has clearly shown damage by CAP treatment to the cell wall of Bacillus stearothermophilus before the plasma membrane was damaged37 and further indications that the bacterial cell wall is an important target during plasma interaction have been reported1314.…”
Section: Discussionmentioning
confidence: 97%
“…used reactive molecular dynamics simulations to show interactions of plasma species with peptidoglycan. It was shown that plasma species can break structurally-important bonds of peptidoglycan, ultimately leading to cell death13. Specifically, it was demonstrated that the presence of OH and O lead to C-O, C-N and C-C bond breakage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cell walls of Gram-positive bacteria consist of peptidoglycan with a tight structure and strength, while Gram-negative bacteria are covered by a thin layer of peptidoglycan and an outer membrane of lipopolysaccharide. During plasma treatment, generated ROS can react with both lipopolysaccharide and peptidoglycan, thus breaking the molecular structure by damaging COO, CON, and COC bonds (32)(33)(34). However, obvious leakage was observed from E. coli only.…”
Section: Discussionmentioning
confidence: 99%
“…As the forces on the atoms and thus the entire system dynamics depend on the latter, it is clear that this is the most crucial aspect of classical reactive MD simulations. There exist several reactive force fields in literature, but in the context of plasma medicine, only the Brenner potential and the ReaxFF potential have been applied.…”
Section: Introductionmentioning
confidence: 99%